Tingkat Serangan Penyakit Busuk Buah (Marasmius palmivorus Sharples) Pada Jarak Tanam (Kerapatan) Yang Berbeda dan Hubungannya Dengan Kehilangan Hasil Kelapa Sawit (Elaeis guineensis Jacq) - Junepri, Junepri; Asniwita, Asniwita; Wilyus, Wilyus (Universitas Batanghari, 2024)
Indonesia is the producer and exporter of palm oil in the world from 2008 - 2023. One of the challenges in managing plantations is pest attacks and plant diseases. The disease that is often found is fruit rot disease caused by the fungus Marasmiuspalmivorus which can reduce production by up to 25% with symptoms of fruit changing color to blackish brown, watery and rotting. One of the factors that influences the development of fruit rot disease is the microclimate (temperature and humidity) around the plant. Microclimate is closely related to plant spacing density. If the plant spacing is tight, the temperature around the plant will be lower and the humidity will be higher, which can trigger the development of fruit rot disease. The research was conducted at PT. Sumatra Jaya Agro Lestari (SJAL) 2 at a density of SPH 160 and SPH 200 which shows that disease intensity and yield loss is higher at SPH 200 where the average disease intensity is 25.13% based on the regression equation with an estimated yield loss of 14.12%. Meanwhile, SPH 160 average disease intensity was 14.33%, with an estimated yield loss of 8.28%. The t test shows that the intensity and percentage of fruit rot disease differ based on plant density.Key words: Oil palm, density, fruit rot, intensity and yield loss